State and culture - Ahmed, Emajuddin; Harun-or-Rashid, 1954; Asiatic Society of Bangladesh (Dhaka : Asiatic Society of Bangladesh, 2007)
Contributed articles published under the Cultural Survey of Bangladesh Project; covers the period, prehistoric times to 20th century.
Includes bibliographical references and index.
Keywords: Bangladesh -- History